Devastating grace: Justificatio impii and I-dentity - Theron, PF (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
It is argued that personal identity and Christian identity are intimately related. Personal identity is fundamentally a forensic issue, which is dealt with in the doctrine of justification as the articulus stantis et cadentis ecclesiae. Christian identity is located extra nos in Christ. In his cross the idolatrous self is shattered and simultaneously re-centred and thus liberated from sinful self-love and self-hate. Our true identity remains an eschatological reality, which will be revealed as part of the cosmic new creation.